Responsible digital communication, infographics and organizations. : The case of Mexico in social networks - Rivera Salas, Paola Eunice (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Objective: To describe the presence of Responsible Digital Communication (DigRC) in infographics disseminated by organizations of various kinds on the social network Facebook. Methodology: Quantitative, descriptive, cross-sectional, and non-experimental, through convenience sampling, taking four Mexican organizations from different sectors. Results: Organizations publish high-quality infographics, but there is a lack of information referents to support their content. Furthermore, the scarcity of feedback affects traits such as Credibility and Reputation of institutions. Conclusion: Analyzing the incidence of digital tools in virtual environments helps to enhance the benefits that their socialization provides to organizations.